1934
DOI: 10.1002/cber.19340670709
|View full text |Cite
|
Sign up to set email alerts
|

Über hochpolymere Verbindungen, 94. Mitteil.: Über ein unlösliches Poly‐styrol

Abstract: l) 03. Mitteil. vorstehend. *) rergl. unsere fruheren Mitteilungen iiber das Poly-styrol im Buch von €1. S t a nd i n g e r : Die hochmolekularen organischeii Verbindungen -Kautschuk und Cellvlose (Verlag S p r i n g e r , Berlin 1932), S. 1j7. 3, vergl. P. B a r y , Rerue g6n. Caoutchouc 2, S r . 2 , S. 5, Nr. 21, S. 3 [1926]; weiter P. B a r y u. E. A. H a u s e r , Kautschuk 1928, 97. 4, vergl. H. S t a u d i n g e r LI. H. F. B o n d y , A. 488, 153 [I931]; H. S t a u d i n g e r u. E. 0. L e u p o l d , B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

1936
1936
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 16 publications
0
43
0
1
Order By: Relevance
“…Staudinger and Heuer [2] could show that this insolubility was due to small amounts of tetrafunctional divinylbenzene present in styrene as an impurity from its synthesis. As little as 0.02 mass % is sufficient to make polystyrene of a molecular mass of 2001000 insoluble [3].…”
Section: Historymentioning
confidence: 98%
“…Staudinger and Heuer [2] could show that this insolubility was due to small amounts of tetrafunctional divinylbenzene present in styrene as an impurity from its synthesis. As little as 0.02 mass % is sufficient to make polystyrene of a molecular mass of 2001000 insoluble [3].…”
Section: Historymentioning
confidence: 98%
“…The first reports of mechanochemistry date back to Staudinger and the observation that high shear forces can induce a decrease of the molecular weight of poly(styrene) on account of the mechanically induced scission of covalent bonds . The deliberate force‐induced cleavage of polymers at specific active sites is a much more recent development .…”
Section: Mechanically Induced Cleavage Of Covalent and Noncovalent Bondsmentioning
confidence: 99%
“…In practice, yw is taken to be the weight-average degree of polymerization of the homopolymer from the monovinyl monomer polymerized under the same conditions. Equation (1) presupposes that the following conditions are met: first, the vinyl groups in the system are of equal reactivity; second, the pendent vinyl group of a singly reacted divinyl monomer is consumed only in interchain polymerization. Walling showed that eq.…”
Section: The Problem Of Gelationmentioning
confidence: 99%
“…&'lory's equation' relating the gel point to the amount of crosslinker and chain length of the uncrosslinked polymer states that: au = (TWX&l (1) where au is fractional conversion at the gel point, X D is the fraction of double bonds belonging to the divinyl monomerh the mixture, and TW is the weight-average degree of polymerizatioh of the "backbone chain." In practice, yw is taken to be the weight-average degree of polymerization of the homopolymer from the monovinyl monomer polymerized under the same conditions.…”
Section: The Problem Of Gelationmentioning
confidence: 99%